Printing soil: a single‐step, high‐throughput method to isolate micro‐organisms and near‐neighbour microbial consortia from a complex environmental sample. Issue 2 (26th November 2014) - Ringeisen, Bradley R.; Rincon, Karina; Fitzgerald, Lisa A.; Fulmer, Preston A.; Wu, Peter K.
Summary: Traditional high throughput methods for isolating microorganisms from environmental samples such as soil or sediment require pre‐processing steps to remove the living species from their solid‐phase microniche, creating a liquid‐phase sample. This process destroys near‐neighbor relationships that could be crucial to culturing and studying the microorganisms to be isolated. An automated, high throughput method is described here that isolates pure microbial cultures and spatially related microbial consortia directly from a solid‐phase complex environmental sample. By using an orifice‐free printing mechanism, Biological Laser Printing (BioLP) enabled single‐step isolation of viable environmental microorganisms directly from soil. Soil was spread onto a titania‐coated quartz plate prior to initiating printing of soil micro‐particles with focused ultraviolet laser pulses. Tunable amounts of soil were printed to glass slides, Luria Bertani agar plates and broth filled 96‐well plates at deposition rates exceeding 20 micro‐particles per second, demonstrating the ability to isolate thousands of micro‐particles of soil in minutes. Viability, culturability and significant morphological diversity were demonstrated post‐printing. Results show that single step soil printing can be used to (a) generate pure microbial cultures (isolates), and (b) isolate consortia from a micro‐ecological system that exists naturally in near‐neighbor proximity, undisturbed from the environmental sample.